Computing Essentials 2005 - O'Leary, Timothy J. and O'Leary Linda I. (Boston McGrawHill, 2005)
Offering a visual orientation that gives students an understanding of computing concepts, this text gives a snapshot of computing. When bundled with software application lab manuals, students are given a representation of the fundamental issues surrounding the personal computing environment.
Includes Appendix, Glossary, Index and Colored Illustrations.
Keywords: Electronic Data Processing